The reality of sociological knowledge in Algeria between production and consumption - Dennaka, Ahmed; Mokhnene, Tarek (Journal of Human Sciences, 2022)
This article discusses the role of the sociological researches and the extent of their integration and response to various issues and problems of Algerian society; known that the field of sociology is the field most familiar with the aspects of society because of its techniques and approaches that qualify it for that. In this article multivariate analysis was adopted in order to obtain results using a questionnaire that includes 52 distributed questions divided on three sections. The analysis of results shows that the sociological researches mostly do not respond to the Algerian problems or otherwise sociological studies rarely take into consideration.